Morphological disparity and systematic revision of the eocrinoid genus Rhopalocystis (Echinodermata, Blastozoa) from the Lower Ordovician of the central Anti-Atlas (Morocco). (10th May 2017) - Allaire, Ninon; Lefebvre, Bertrand; Nardin, Elise; Martin, Emmanuel L.O.; Vaucher, Romain; Escarguel, Gilles
Abstract: The genus Rhopalocystis (Eocrinoidea, Blastozoa) is characterized by both a short stratigraphic range (Fezouata Shale, middle Tremadocian to middle Floian, Lower Ordovician) and a reduced geographic extension (Agdz-Zagora area, central Anti-Atlas, Morocco). Since the original description of its type species ( R. destombesi Ubaghs, 1963), three successive revisions of the genus Rhopalocystis have led to the erection of nine additional species. The morphological disparity within this genus is here critically reassessed on the basis of both historical material and new recently collected samples. The detailed examination of all specimens, coupled with morphometric and cladistic analyses, points toward a relatively strong support for five morphotypes. A systematic revision of Rhopalocystis is thus suggested, with only five valid taxa: R. destombesi, R. fraga Chauvel, 1971, R. grandis Chauvel, 1971, R. havliceki Chauvel, 1978, and R. zagoraensis Chauvel, 1971. The five others are considered as junior synonyms ( R. dehirensis Chauvel and Régnault, 1986, R. lehmani Chauvel and Régnault, 1986, R . sp. A, R . sp. B, and R . sp. C).